The rifleman - North, Oliver (Fidelis Books, 2019)
"This is a war story. It's about real people and events before and during the American Revolution. The central characters in this work, Daniel Morgan, George Washington, Patrick Henry, Charles Mynn Thruston, and Generals Arnold, Knox, Greene, Lee, Gates, and a host of others, actually did the deeds at the places and times described herein. So too did their accurately identified foreign and native adversaries. Though this is a work of fiction, readers may be surprised to discover the American Revolution was also one of the most 'un-civil' of Civil Wars. If Daniel Morgan were alive today, he would be my near neighbor in Virginia's beautiful Shenandoah Valley. While visiting a nearby gristmill, Daniel Morgan and Nathaniel Burwell, a fellow Revolutionary War veteran, built in the late 1700s (now restored and operated by the Clarke County Historical Association), I became fascinated by this unsung American hero."--Amazon.